THE TWO FUNDAMENTALS OF HUMAN DEVELOPMENT (TAMADDUN NURI JURNALI, 2024)
This article reveals the religious and secular aspects of Mahmud az-Zamakhshari's socio-philosophical views. At the same time, Mahmud az-Zamakhshari's entry into the world of science, the main features of his superiority over other professions, and his views that science can glorify man and raise him to the level of perfection are revealed on the basis of analysis.